THEORETICAL DESCRIPTION OF THE MARKETING SYSTEM OF AUTOMOTIVE ENTERPRISES - Zaynutdinova, Umida (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article examines the issues of using benchmarking to increase the competitiveness of auto industry enterprises. In the present conditions, the idea of the interaction concept in the marketing activities of auto industry enterprises consists of relations (communication) between buyers and the participants of the buying and selling process, scientific proposals and recommendations are given to increase the importance of effective communication of marketing interaction.